Current Opinion of Obstetricians on the Prescription of Emergency Contraception: A German-American Comparison - David, M.; Berends, L.; Bartley, J. (Geburtshilfe und Frauenheilkunde, 2012)
Background: There are no current studies on the opinions of obstetricians and gynaecologists in Germany about emergency contraception (or post-coital contraception, morning-after pill). The opinions of a large group of physicians were collected using of a questionnaire and compared with the results of an American survey (n = 1154). Methods: A two-part questionnaire was used – part 1: sociodemographic data, part 2: 4 scenarios to illustrate the possible advantages and disadvantages of free access to emergency contraception as well as 4 indications and situations for which emergency contraception can be prescribed. Results: The response rate was 91.7 % (165/180 questionnaires). 63.9 % (103/161) of the German responding physicians were of the opinion that women with access to emergency contraception experienced unwanted pregnancies less frequently than those without access. Merely 26.2 % of the responding physicians supported the prescription-free availability of emergency contraception in apothecaries. The German-American comparison ultimately revealed only a few major differences, e.g., in answers to the question whether or not access to emergency contraception could reduce the number of unwanted pregnancies (89 vs. 64 %). Conclusions: The high rejection rate of free access to emergency contraception of almost 70 % in our surveyed group supports the current position published by the German Society for Gynaecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe) and the German Professional Union of Gynaecologists (deutscher Berufsverband der Frauenärzte). Since other medical organisations, e.g., WHO, supported the prescription-free access to levonorgestrel formulations as emergency contraception a few years ago, it would be interesting to ask a larger sample of German gynaecologists and obstetricians about their opinions on emergency contraception.
Keywords: emergency contraception; physician questionnaire; levonorgestrel; ulipristal